VIRTUAL TOUR: A MEDIA TO TEACH ENGLISH FOR TOURISM - Sutrisno Sadji Evenddy; Ledy Nurlely (Jurnal Visi Ilmu Pendidikan, 2022)
This study aims at explaining the use of virtual tours in learning English for tourism in the English for Tourism course at the Department of English Education, Sultan Ageng Tirtayasa University. Technology is an alternative that is used as a human response. In the field of education, innovation was born through technological developments, namely virtual tour services which became a learning platform equipped with visual, audiovisual and interactive learning resources. Studying at home can be boring for both students and teachers due to the confined environment in the room. It is hoped that the visual service organized by the virtual tour application in Indonesia can provide educational, inspirational and recreational value as well as in learning English for tourism which is carried out online